Labour Earnings Identity - McKee, A. (Relations industrielles / Industrial Relations, 1973)
An earnings identity may be constructed to relate consistently changes in factor earnings, share of income, productivity, unit costs and price deflator. The case of labour is the most relevant, and is readily illustrated by using GNP and Labour Force statistics. These 'global' changes may be linked up in workable fashion with changes in the Consumer Price Index and wage statistics. The attempt to refine the terms of the identity introduces problems of consistency of definition and improves Utile on the crude results.